Effect of Pseudomonas colonisation on lower limb venous ulcer healing: a systematic review. (2nd February 2022) - Toale, Conor; Kelly, Aisling; Leahy, Fiona; Meagher, Helen; Stapleton, Patrick J; Moloney, Michael A; Kavanagh, Eamon G
Abstract : Objective: Pseudomonas aeruginosa is a Gram-negative bacillus that commonly colonises lower limb venous ulcers. Its effects on venous ulcer healing are widely debated. It produces exotoxins and elastase, as well as forming biofilms in hard-to-heal wounds. It is postulated that these virulence factors lead to slower healing times in patients with lower limb venous ulcers colonised with Pseudomonas . This review aimed to summarise the available evidence pertaining to this topic. Method: A systematic review was performed in August 2019, where the Pubmed, Cochrane and Embase databases were searched for relevant literature according to PRISMA guidelines. Retrospective and prospective studies examining the effect of Pseudomonas colonisation on any measure of ulcer healing were included. Results: Some 282 articles were screened, of which seven studies including 491 patients were ultimately included for analysis. Of these, no study demonstrated a significant association between Pseudomonas colonisation and delayed healing of venous ulcers. In five of the seven studies, the effect of Pseudomonas aeruginosa on initial ulcer size at presentation was recorded. Conclusion: All the studies demonstrated an association between ulcer size and the presence of Pseudomonas aeruginosa . While Pseudomonas aeruginosa may colonise larger ulcers or those with a worse prognosis, no evidence was found to support the hypothesis that this colonisation had a negative impact on lower limb venous ulcer healing.